Use of solar energy for disinfection of polluted water - Y. Jamil (Soil & Environment, 2009)
Polluted water is causing serious health problems especially in the rural areas of Pakistan. People have limited access to safe water supply and many diseases like diarrhea and gastrointestinal diseases are transmitted by consumption of polluted water. We have investigated the potential of using solar energy to pasteurize water. Low cost indigenously available materials have been utilized to design and fabricate a solar box type pasteurizer having a capacity of three liters. The performance study of the pasteurizer was performed during the month of May 2008. The designed pasteurizer maintained water temperature in the range of60 oC to 70 oC continuously for more than an hour which is enough for deactivation of coliform bacteria. The maximum water temperature on a clear sunny day was found to be 67 oC, corresponding to an ambient temperature of40 oC. With the pasteurizer facing south, a very little repositioning was required. The low cost and operational simplicity of the pasteurizer make it affordable and usable. It is more useful in rural areas where other sources of energy like electricity and gas are not easily available